To Each Their Own: The Impact of Regulatory Focus on Consumers’ Response to Online Information Load - Peng, Minjing; Xu, Zhicheng; Huang, Haiyang (Frontiers in Neuroscience, 2022)
Contrary to the common view that more information is always better, too much information can damage decision quality. Building on existing literature, this study identified regulatory focus as a critical factor influencing the effect of information load (IL) on online consumer decisions and used event-related potentials (ERPs) to uncover its underlying neural mechanism. Behavioral data showed that promotion-focused participants would spend less time making purchasing decisions in the low IL condition than in the high IL condition. However, no significant difference was found for prevention-focused participants. In contrast to the high IL condition, ERP data indicated that the low IL condition recruited more attentional resources at the early stage of rapid automated processing (larger P2 component), led to reduced long-term memory conflict (smaller N2 component), and resulted in enhanced decision confidence (larger P3 component) for those with a promotion focus. However, we observed either weakened or even opposite outcomes for those with a prevention focus. These findings generally shed light on when e-retailers should provide large/small amounts of product information in online environments.